RESPONSIBILITY IN CONSTRUCTION LAW - Ziemele, Ināra (Administrative and Criminal Justice, 2023)
The new Construction Law and others Construction Regulations come into force on 01.10.2014. to define responsibility of construction specialists and institutions. Since then passed more than two years and responsibility of construction still is an important question in construction. The aim of paper is to summarize information about how responsibility is working in practice. Research focuses on how responsibility which is regulated by the new regulatory enactments matches with situation in practice. There are used methods of historical research, analysis, comparative analysis, systematic text condensation and theoretical method of research to investigate, analyse and summarize information of publications and regulatory enactments about responsibility and situation in practice. The main conclusion shows that there is not clearness about responsibility of every person in construction and responsibility which is regulated by the new regulatory enactments is not properly working in practice.